A formação de servidores da educação profissional e tecnológica em debate: uma proposta a partir da plataforma Moodle - Marinho, Jéssica Reis (2021)
This research, carried it out within the scope of the Professional Master's Degree in the Professional and Technological Education in The National Network (ProfPTE), it deals with the training of public employees to work in professional and technological education (PTE). That’s why includes the history and foundations of the PTE as a public policy socially referenced. The training of educators to work in the area is still a challenge to the Federal Network of Professional, Scientific and Technological Education (FNEPSTE). The scenario of the discussions and the research locus is the Federal Institute of Amazonas (IFAM), Campus Parintins. In addition, it aims to investigate how IFAM has provided training experiences in PTE to its employees, with a view to prepare them for the offer of a teaching based on the integral training of students. In this sense, qualitative research was chosen as the typology of this investigation which treatment and analysis of the data were embodied through the Bardin Content Analysis method (2011). The process of categorization of the collected corpus generated two themes of analysis that approaches the "training experiences in PTE" through which the employees have been passed by and their "perceptions" about the field of professional and technological education. These analysis themes provide data that reveal whether they have experienced specific formative processes in PTE throughout the professional practice in the face of other types of training, as well as the knowledge accumulated in the area, in addition, knowledge in PTE has been applied in their professional practices. Among the main discoveries, it is highlighted that few formative experiences have been specifically focused on the conceptual understanding of PTE, including its bases, foundations and history. And that has reflected in the perceptions of the employees about the PTE policy in regarding to the accumulated knowledge about the area and how they have applied the knowledge in their work activities as educators. The term "educator" is used here for both teachers and administrative technicians in education (ATE). It is concluded that the training of servers channels in PTE, within the scope of IFAM–CPA, need to be expanded with a view to democratize knowledge of extreme relevance for the development of the professional practice of educators, as well as contributing to the strengthening of the political-pedagogical aspect that seeks to offer unilateral training to students in counterpoint to the alienating pragmatism that persists in the arena of dispute of curricula within the policy of the professional education. The results of the research also supported the materialization of the educational product called "Introduction to the history of the Professional and Technological Education in Brazil and its Conceptual Bases" which target audience are the area educators, especially those of IFAM, and which aims to provide a basic training tool on these topics.